Second-Sourcing as a Commitment: Monopoly Incentives to Attract Competition - Farrell, Joseph; Gallini, Nancy T. (Quarterly Journal of Economics, 1988)
We show that a new product monopolist may benefit from (delayed) competition if consumers incur setup costs. Setup costs create a dynamic consistency problem: the monopolist cannot guarantee low future prices once customers have incurred those costs. We show that, if customers anticipate this problem, the monopolist's profits can be improved through ex ante commitment to competition in the post-adoption market, if setup costs are large. If setup costs are small, the monopolist can typically achieve the same level of profits without price commitment as with.